Undetected Cortrak tube misplacements in the United Kingdom 2010–17: An audit of trace interpretation. (December 2019) - Taylor, Stephen J.; Allan, Kaylee; Clemente, Rowan
Abstract: Objectives: Determine why Cortrak-guided, undetected tube misplacement may occur in relation to the system of trace interpretation used. Methodology: From 2010 to 2017 we obtained seven of the eight Cortrak traces from the United Kingdom where misplacement was undetected and the patient received feed. Seven suffered serious harm. Each misplacement was interpreted by three systems: screen position, manufacturer guidance and gastrointestinal (GI) flexures. Setting: National and local records. Main outcome measures: Ability to identify misplacement. Results: Traces that were later identified as misplacements, could not be differentiated from GI position when they wholly or partially: a) overlapped with the GI screen area plotted from historical records (57–71%) or b) met both manufacturer guidance criteria or were confused with receiver misplacement or unusual anatomy and reached the lower left quadrant (14–71%). Conversely, all lung misplacements were identified as unsafe using the GI flexure system. All three systems failed to detect the intra-peritoneal trace. Traces were inconsistently stored by healthcare centres. Conclusion: Trace file storage should be mandated by and accessible to relevant health authorisation bodies to improve safety research. Screen position alone and manufacturer guidance fail to consistently differentiate the shape of safe from unsafe traces. GI flexure interpretation appears safer but requires testing in larger studies.